Mobilidade engajada na alfabetização de adultos do MTST: uma investigação durante a pandemia de Covid-19 - Santos, Lucas Régis dos (2021)
This research aimed at identifying MTST students’ needs to create a lesson plan, based on a social activity, contemplating these subjects’ educational specificities, during the Covid-19 pandemic period. The study was conducted by the question: how to build a lesson plan for adult literacy, based on multiliteracies pedagogy and aimed at engaged mobility, which contemplates MTST young adults’, adults’, and elders’ necessities? Data collection and production used structured and semi-structured questionnaires for interviews performed in person and through phone calls, as well as it relied on the daily contact with MTST Literacy Brigade members in Guarulhos and São Paulo camps, during the years of 2019-2020. Critical-collaborative Research was used as theoretical-methodological approach, since the study focused on collective construction, with MTST members, of critics and transformation for Building a different model of Society. Data analysis was approached by Social-Historical-Cultural Activity Theory, Social Activity and Multiliteracies Pedagogy. Among others, results found that students, in general, show difficulties in moving around the city, reading patient information leaflets in medication, and reading the bible at the church. They also missed job opportunities because of their lack of literacy or gave up going to college. The social activity proposed as an example and based on observation, analysis, and daily contact with the students, therefore, used the theme: Going to work. Educational training proposal dealt with multiliteracies and the social activity in a way to produce resources and tools for the educators in service, so that they could, along with the students, develop engaged mobility in the participants